2014
DOI: 10.1007/s11695-014-1524-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy for Morbid Obesity with Intra-operative Endoscopy: Lessons We Learned After 100 Consecutive Patients

Abstract: Sleeve gastrectomy with intra-operative endoscopic guidance is at least as safe and effective as with the bougie. Given the available expertise and equipment, the use of this technique can increase the intra-operative sense of safety with no compromise or even improvement of the immediate or long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…A meta-analysis reported that, in %EWL terms, bariatric surgery is more effective in Caucasians than in blacks, regardless of procedure type [33]. Studies on LSG have also reported that the weight loss outcomes were significantly less favorable for super-obese patients as well as older patients [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis reported that, in %EWL terms, bariatric surgery is more effective in Caucasians than in blacks, regardless of procedure type [33]. Studies on LSG have also reported that the weight loss outcomes were significantly less favorable for super-obese patients as well as older patients [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates (n = 79), the 1554 records were screened by title and abstract after which 1179 were excluded and the full-text articles for the remaining 375 records were assessed for eligibility. A total of 148 papers were included in the final analysis and the number of studies per reinforcement method were: 69 for NO-SLR [9, 17-84], 70 for suture [9,19,20,22,26,30,46,51,53,75,76,78,83,, 9 for BPS [9,72,78,83,86,89,[141][142][143], 9 for Seal [9,30,61,74,78,103,[144][145][146], and 24 for APM [9,39,52,53,63,89,103,131,[147][148][149][150][151][152][153][154][155][156][157][158][159][160]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[3] Conversely, the use of intraoperative endoscopy for the calibration of the stomach has sparsely been reported. [4] The calibration with bougie during LSG is rarely related to complications. [5] However, this technique can lead to complications such as accidental stapling across the tip, staple-line corkscrewing and esophageal perforation (EP).…”
Section: Introductionmentioning
confidence: 99%